Institutional Learning and Change: an initiative to promote greater impact through agricultural research for poverty alleviation - Watts, Jamie; Horton, Douglas (2008)
The ILAC Initiative consists of an evolving community of individuals committed to increasing the contributions of agricultural research to sustainable poverty reduction around the world. ILAC promotes research, methodology development and capacity development to increase understanding of agricultural change processes and increase the effectiveness of interventions to stimulate pro-poor innovation. This paper presents a broad overview of ILAC, including its background, origins and evolution, objectives and activities. It also presents the initiative’s central hypothesis and a set of guiding questions. Theoretical frameworks that show promise for increasing understanding of issues related to capacities to learn, facilitate innovation, and contribute to poverty reduction are introduced.